2005
DOI: 10.1002/chem.200500046
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Materials and Living Organisms: Surface Modifications and Fungal Responses to Various Asbestos Forms

Abstract: In a previous study several strains of soil fungi were reported to remove iron in vitro from crocidolite asbestos, a process that was envisaged as a possible bioremediation route for asbestos-polluted soils. Here, we get some new insight into the chemical basis of the fiber/fungi interaction by comparing the action of the most active fungal strain Fusarium oxysporum on three kind of asbestos fibers--chrysotile, amosite, and crocidolite--and on a surface-modified crocidolite. None of the fibers examined signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 53 publications
5
26
1
Order By: Relevance
“…Chemical modifications in crocidolite were not previously detected in crocidolite fibres inhaled by rats after 365 days [49]. By contrast, a significant release of Fe in culturing solutions was detected when fibres were incubated with soil fungi in laboratory experiments, thus suggesting an iron extraction due to siderophore-like molecules or acidic metabolites [50][51][52]. The depletion of Na, which occupies exposed sites along the 110 mineral cleavage plain [53], and the trend towards a decrease in the FeO tot content which are determined by Acarospora may follow a similar mechanism driven by lichen metabolites.…”
Section: Sem-eds Analysis Of Fibre Weathering By Lichenscontrasting
confidence: 62%
See 1 more Smart Citation
“…Chemical modifications in crocidolite were not previously detected in crocidolite fibres inhaled by rats after 365 days [49]. By contrast, a significant release of Fe in culturing solutions was detected when fibres were incubated with soil fungi in laboratory experiments, thus suggesting an iron extraction due to siderophore-like molecules or acidic metabolites [50][51][52]. The depletion of Na, which occupies exposed sites along the 110 mineral cleavage plain [53], and the trend towards a decrease in the FeO tot content which are determined by Acarospora may follow a similar mechanism driven by lichen metabolites.…”
Section: Sem-eds Analysis Of Fibre Weathering By Lichenscontrasting
confidence: 62%
“…Moreover, lichens, by physically contacting the fibres, chemically modify their composition. Laboratory experiments showed that modifications in the chemical composition of chrysotile and crocidolite, similar to those we detected below lichens on asbestos-cement, affect their surface chemistry, determining a decrease of their Fenton activity [24,27,51,52], i.e. one of the main factors currently related to asbestos toxicity [5,6,37].…”
Section: Discussionmentioning
confidence: 89%
“…[13] In this context, soil fungi have recently been reported by some of us to modify the chemical composition of asbestos fibres. [16][17][18][19] The symbiotic lichen-forming fungi are well-known physical and chemical weathering agents of natural and artificial mineral substrata. [20,21] Besides the physical effects related to the penetration of fungal hyphae, lichens chemically deteriorate minerals by secreting a wide range of primary and secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Release of siderophores by some fungal species [1,12] was effective in reducing cytotoxicity of chrysotile asbestos in in vitro conditions. The damaging effect on naked DNA in in vitro situations was reduced by removal of iron from asbestos, by fungi belonging to Verticillium species, Paecilomyces species and Fusarium oysporium [4].…”
Section: Fig 1 Rajsamand and Jodhpur Districts Of Rajasthanmentioning
confidence: 98%
“…Its low cost has further made its applicability extensive, ever since the industrial revolution. Found mainly in serpentine [1] and amphibole rocks [2], it is categorized into six types based on the chemical composition. They are chrysotile (white asbestos), crocidolite (blue asbestos), amosite (brown asbestos), tremolite, anthophyllite and actinolite.…”
Section: Introductionmentioning
confidence: 99%